Chronology of the Reigns and Personalities of the Rulers of the Crimean Khanate in 1475–1478 » - V.P. Gulevich (Золотоордынское обозрение)
Captivated Mengli Giray remained the Crimean Khan nominally and lived more than a year under the full control of the Turks, probably in Caffa. Crimean Karachi-beys were united against Eminek during the struggle for power. As the result of their efforts, the «Cossack» prince Dzhanibek, the son of Akhmad Khan, became the Crimean ruler, independent from the Great Horde and the Ottoman Empire. Since he ruled as a sovereign ruler, Meñli’s stay in the Crimea lost sense and he was taken to Turkey in October–November 1476. In the late summer and early autumn 1477 Djanibek lost power under unknown circumstances and went to Moscow. Power in the Crimea was shared between Nur-Devlet and Idar. This probably happened with the assistance of Prince Abdullah and Barin Yamgurchi. After Eminek had lost his influence on khans, he fairly quickly managed to destabilize situation or use the unstable situation in the Crimea for his own purposes and, with the consent of the Turkish sultan, he once again brought to power Meñli Giray in the late 1478 or early 1479.